2015
DOI: 10.1007/s11606-015-3369-4
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on Diagnostic Errors: Taking a Second Look is Not Enough

Abstract: BACKGROUND: An experimenter controlled form of reflection has been shown to improve the detection and correction of diagnostic errors in some situations; however, the benefits of participant-controlled reflection have not been assessed. OBJECTIVE: The goal of the current study is to examine how experience and a self-directed decision to reflect affect the accuracy of revised diagnoses. DESIGN: Medical residents diagnosed 16 medical cases (pass 1). Participants were then given the opportunity to reflect on each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 25 publications
3
55
1
1
Order By: Relevance
“…16 Several studies have tried to encourage reflective practice and System 2 processes by instructing participants to proceed slowly through their reasoning 18 or by giving participants the opportunity to review their diagnoses. 19 These studies have found minimal or no impact on reducing the rate of diagnostic error. On the other hand, some studies have shown improved diagnostic accuracy when physicians are asked to explicitly state their differential diagnoses along with features that are consistent or inconsistent with each diagnosis.…”
Section: Improving Clinical Reasoningmentioning
confidence: 99%
“…16 Several studies have tried to encourage reflective practice and System 2 processes by instructing participants to proceed slowly through their reasoning 18 or by giving participants the opportunity to review their diagnoses. 19 These studies have found minimal or no impact on reducing the rate of diagnostic error. On the other hand, some studies have shown improved diagnostic accuracy when physicians are asked to explicitly state their differential diagnoses along with features that are consistent or inconsistent with each diagnosis.…”
Section: Improving Clinical Reasoningmentioning
confidence: 99%
“…Research demonstrates that some stress and thoughtful reflection are beneficial to the thinking process, 2-4 yet there is no consensus on how to positively manage stress or use reflection in daily clinical care. Two articles 5,6 in this issue of JGIM explore the areas of stress and reflection on critical thinking among trainees.The study by Pottier and colleagues 5 explored the role of stressors on a medical student's history taking, physical examination, and clinical reasoning. The authors performed a study of medical students who participated in two scenarios with standardized patients with familiar disease processes.…”
mentioning
confidence: 99%
“…Research demonstrates that some stress and thoughtful reflection are beneficial to the thinking process, 2-4 yet there is no consensus on how to positively manage stress or use reflection in daily clinical care. Two articles 5,6 in this issue of JGIM explore the areas of stress and reflection on critical thinking among trainees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Montiero et al reported in this issue suggests that instructing resident physicians to reflect on the most likely diagnosis and giving them more time in the analytical mode does not increase the likelihood that the correct most likely diagnosis will be reached. 5 Classifying medical education research according to its purposes illuminates three levels: the individual study level, the body of studies focusing on the topic, and the entire enterprise of medical education research. Studies that have made the greatest contributions to our knowledge are characterized by a cycle of observation, formulation of a model or hypothesis to explain the results, and predictions of what will happen that are based on the model.…”
mentioning
confidence: 99%